Peningkatan Kolaborasi Generasi Z Di Lingkungan Pendidikan Dengan Menerapkan SIM Berbasis Cloud Computing - Desinawati Desinawati; Feby Budi Setiawan; Tutut Setiarini; Susandri Susandri (Jurnal Ekonomi dan Bisnis Digital, 2024)
The research was to analyze the relationship between SIM, Cloud Computing and Generation Z collaboration in the school environment, with a focus on SMK Muhammadiyah 1 Pekanbaru. The research method applied is quantitative, it is done by collecting data on answers filled in by students in answering the distributed questionnaires. Likewise for data collected with teacher respondents. The analysis results show that the implementation of a cloud-based management information system has succeeded in increasing collaboration between students and between students and teachers, with a measurable increase in collaboration reaching 85%. These findings indicate that the integration of cloud computing technology in educational systems not only facilitates better communication, but also supports the development of collaborative skills of generation Z. This research recommends further implementation of cloud-based systems to improve the efficiency and effectiveness of learning in educational institutions.